Cirebonese-English Code Switching in English Teaching-Learning Process in SMAN 1 Jamblang, Cirebon Regency - Ervina C M Simatupang; Hero Gunawan; Dianita Dianita; Susiyanti Susiyanti (Pusat Studi Bahasa dan Publikasi Ilmiah, 2023)
Code switching nowadays is more of the norm than the exception for people who speak more than one language. In case of a foreign language teaching-learning process, both of students and teachers are commonly mixing the foreign language they learn with their mother (first) language, as found in English teaching-learning process at Public Senior High School, SMAN 1 Jamblang, in Cirebon regency, West Java, Indonesia. They usually switch English speech with their mother language, Cirebonese language. This paper aims to analyse the function of code switching in the English teaching-learning activity at SMAN 1 Jamblang and see how effective it is to help students’ understand the English subject. The data were collected by observation and documentation and then, analysed using Sociolinguistics approaches, namely social factors theory proposed by Holmes (2001), referring to switch code functions developed by Reyes (2004) and Ajmal (2010), who did the related studies. The research results show that the code switching has two functions, namely delivering the material effectively and managing the class. Furthermore, based on survey on the students at SMAN 1 Jamblang, it shows that more than 93% of respondents strongly agree that the use of code switching helps developing students’ understanding the English subject.